Clarification des positions sur la laïcité et objectivation des idéologies, un double enjeu dans l’École et pour l’École - Xavier Riondet; Bérengère Kolly (Éducation et Socialisation)
The Ministry of National Education in France engaged in several important workstreams – secularitsm in School, digital literacy, encouragement to critial thinking). But some important issues have to be resolved. This article crosses historical and philosophical approaches in order to understand the situation of many teachers who must pass on the message on secularism. It is necessary to demarcate the context to understand a practical problem : there is a gap between convainced of secularism teachers and a secularism which doesn’t make sens for a lot of pupils. This article describes the complexity of the situation due to the digital culture ; it proposes then to clarify the positions about secularism, to objectify the different ideologies which can stand in the way of its transmission. This text, finally, proposes several didactic remedies.